PENGARUH METODE BERCERITA TERHADAP PERKEMBANGAN BAHASA ANAK DI KELOMPOK B2 TK ADHYAKSA XXII PALU - Nur Rahma; Intan Permatasari (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2026)
This study is a child's language development has not developed as expected. The aim is to determine the effect of the storytelling method on children's language development. The research method used is a quantitative approach method and an experimental research type. The subjects of this study were children in Group B2 of Adhyaksa XXII Palu Kindergarten, totaling 21 children. Data collection techniques were carried out through observation, interviews, and documentation. Data processing was carried out using percentage techniques and t-tests (paired sample t-test). Data from the recapitulation of observations of children's language development before being given treatment in the form of storytelling methods, in the three aspects that have been observed, there were 0% in the BSB category, 12.70% in the BSH category, 52.38% in the MB category, and 34.92% in the BB category. After being given treatment in the form of storytelling methods, from the results of the recapitulation of observations of children's language development in the three aspects that have been observed, an average of 55.55% was obtained in the BSB category, 22.22% in the BSH category, 22.23% in the MB category, and 0% in the BB category. Based on the results of the t-test calculation data, the value of ttug> ttable (20,088> 1,724) was obtained, and the significance value was 0.000 <0.05. It can be concluded that Ho is rejected and H1 is accepted, which means that there is an influence of the storytelling method on children's language development in Group B2 of Adhyaksa XXII Kindergarten, Palu.